Essential hypertension: a disorder of growth with origins in childhood? - Lever, A F; Harrap, S B (Journal of hypertension, 1992)
To review evidence that essential hypertension is a growth-related disorder with origins in childhood and manifestations in adult life. Blood pressure rises with age in children and adults. In children, the rise closely relates to growth and to skeletal and sexual maturation. Adolescents with highest pressure are heavier and had as children grown fastest; as adults, they show the greatest increase of pressure with age and are more likely to develop hypertension and coronary heart disease. In adults, the rate of increase of pressure relates to earlier pressure. One interpretation of this is that a self-perpetuating mechanism is at work. Genetic and environmental factors influence these events. Most forms of secondary hypertension have two pressor mechanisms; a primary cause, e.g. renal clip, and a second process, which is slow to develop, capable of maintaining hypertension after removal of the primary cause, and probably self-perpetuating in nature. We suggest that essential hypertension also has two mechanisms, both based upon cardiovascular hypertrophy: (1) a growth-promoting process in children (equivalent to the primary cause in secondary hypertension); and (2) a self-perpetuating mechanism in adults.